Analysis Of Mathematical Thinking Ability Of Independent Program Students Learn Independent Campus On Analytic Geometry Courses - Dina Puspita; Isnaini Handayani (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to describe and analyze the mathematical creative thinking skills of student exchange program students who take Analytical Geometry courses in the Mathematics Education study program, Prof. Muhammadiyah University. DR. HAMKA. The research approach used is descriptive qualitative. Subjects were taken by purposive sampling technique. The subjects of this study were 5 students of the non-mathematics education study program who took the analytical geometry course in the mathematics study program. The instrument used in the form of a test description which contains indicators of creative thinking, observation and interviews. Based on the research results , it is known that the average score of students' mathematical creative thinking abilities (non-mathematical) is in the criteria of being quite creative (moderate). The error factor in solving the problem of creative thinking skills in analytic geometry material is that students do not understand the problem well. This shows that students are not used to answering questions that contain indicators of creative thinking